ChemInform Abstract: Microwave Synthesis of 2‐[(E)‐2‐(1H‐Indol‐3‐yl)vinyl]hetarenes. Issue 17 (April 2016) - Aksenov, Alexander V.; Nadein, Oleg N.; Aksenov, Nicolai A.; Skomorokhov, Anton A.; Aksenova, Inna V.; Rubin, Michael A.
Abstract: A new green method for the synthesis of compounds bearing a non‐symmetrical bishetarylethylene structural motif, compounds of great interest for bioorganic and medicinal chemistry, is developed.